PEMETAAN KEMISKINAN DAN OTONOMI DAERAH di PROVINSI BALI DENGAN MULTIDIMENSIONAL SCALING - Yudha, I Made Endra Kartika (Buletin Studi Ekonomi, 2020)
Poverty and regional autonomy have become a hot issue in Indonesia. The problem of poverty has become one of the focuses in both the MDGs and SDGs. Regional autonomy has also become a major concern in the development of government management in Indonesia, given the development of regional autonomy encountered many challenges such as corruption with indicators in the form of regional heads affected by the problem of corruption. For this reason, it is important to mapping and it provides a good visual picture of regional autonomy and poverty. This research is conduct in Bali Province in 2018 using time series data. This study uses multidimensional scaling to map relationships between objects that have similarities. The findings in this study are that regional autonomy does not produce the same relationship with poverty in every region in Bali Province. For low poverty independent regions such as Badung Regency and Denpasar City, it is shown that regional autonomy with a high level of financial independence can produce a low number of poor people compared to other regions in the Province of Bali. There are also findings that there are areas of low poverty independent such as Klungkung, Bangli, and Jembarana districts. This illustrates the impact of autonomy in each region is not the same and high regional financial capacity is not a reference in producing low poverty in an area. This is possible because poverty is a complex problems.